Inspiratory muscle resistance combined with strength training: effects on aerobic capacity in artistic swimmers - Fan, Y.; Duan, Y.; Gao, Z.; Liu, Y. (Frontiers in Sports and Active Living, 2024)
Objective: This study aimed to investigate the effects of combining inspiratory muscle resistance with strength training on lung function and aerobic capacity in artistic swimmers.